Factors influencing intention to use"buy online pickup in-store (bopis)" service for purchasing clothing - Chung, Zheng Hang (2023)
In the ever-evolving landscape of omnichannel retailing, comprehending the fundamental drivers behind the adoption of Buy Online, Pick Up In-Store (BOPIS) becomes crucial as it shapes consumer behavior. This study is designed to identify the factors influencing consumers' intentions to use BOPIS service for clothing purchases with the application of the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) model. Through a quantitative survey method, individuals without prior BOPIS experience were surveyed to examine the role of performance expectancy, effort expectancy, social influence, and hedonic motivation impact their willingness to embrace BOPIS. The empirical data collected through selfadministered questionnaires from 215 valid respondents by using convenient sampling technique and subsequent data analysis was conducted using SPSS software.